Tratamiento quirúrgico directo de las obstrucciones de la Aorta Abdominal y Arterias Periféricas y de las lesiones traumáticas agudas en estos vasos : Reparación de lesiones agudas y crónicas arteriales mediante injertos. (1957)
The author discuss the diagnosis of thrombotic onstructions of the abdominal aorta, iliac arteries and articles and arteries and arteries of the legs by arteriography as well as the surgical treatment of both chronic and large acute lesions by grafting. They have had gratifying results in short segment grafts. Very long by-passing grafts (femoral), have failed due to thrombosis. Saddle embolus of the the patient's condition allows surgery. Anticoagulant therapy should be institud in very bad risk cases or when that limit time has been exceeded.